Physical layer security for wireless networks with help of jamming - Anjos, Gustavo Miranda Castilho dos (2023)
Due to the open nature of the radio environment, the communication over a wireless channel is particularly prone to eavesdropping attacks. To ensure confidentiality, today networks rely on higher layer cryptographic protocols, which provide protection grounding on the assumption that some mathematical problems cannot be solved efficiently using current technologies. However, recent advances in the field of quantum physics established quantum computation as one of the major threats that higher layer cryptographic protocols might face in the near future, as some of these same problems will be solved efficiently with this new form of computation. In this context, the concept of physical layer security emerges as a promising solution to address such concerns by securing wireless channels at the physical layer. The present thesis intends to extend the knowledge on the latter field, giving particular emphasis to the development and analysis of new cooperative jamming techniques. Thereby, to expose the importance of the signal structure on physical layer security, this thesis starts by deriving a closed form solution for the achievable secrecy rate when multiple jammers employ interference alignment in a wiretap channel. The evaluation of this secrecy rate allowed to better understand the relevance of non-decomposable sets on cooperative jamming. Then, assuming a varying channel condition without jamming, the same analysis is carried out considering that proper and improper constellation structures are transmitted coherently with the legitimate link. In this case, it was possible to conclude that the more information is mapped on the signal phase, less information leaks to the eavesdropper. This initial study not only contributed with new theoretical results to the literature, but it also defined some basic ground knowledge for the remaining of the thesis. Following some of that knowledge, a hybrid cooperative jamming scheme is developed next by combining blind jamming with interference alignment. The goal is to protect a broadcast channel from eavesdropping attacks carried out both by registered users and external terminals. The latter work stands out from those found in the literature by proposing a cooperative jamming solution that achieves positive secure degrees of freedom in a more demanding secrecy scenario. The final point addressed in this document analyzes the impact of the channel training phase on physical layer security. In that scope, an innovative secure channel training method is jointly designed with a cooperative jamming technique to improve secrecy on a varying broadcast channel. The evaluation of the latter method revealed that under dynamic channel conditions, limiting the availability of channel information at the eavesdropper can be used to extend the system secrecy.